FEATURES PROMOTION OF HOTEL SERVICES WITH THE USING MODERN MARKETING METHODS - V. Kolobkova; D. Suvorova (Вестник университета)
The arguments proving necessity of promotion of hotel services with the using innovative marketing trends. The carrying out of evaluation key marketing strategies in hospitality industry. The most creative approaches in the marketing policy of the hotel enterprise are allocated.